2005
DOI: 10.1007/s10545-005-4138-z
|View full text |Cite
|
Sign up to set email alerts
|

Globoid cell leukodystrophy (Krabbe disease): Normal umbilical cord blood galactocerebrosidase activity and polymorphic mutations

Abstract: Globoid cell leukodystrophy is an inherited metabolic disorder of the central nervous system caused by deficiency of the lysosomal enzyme galactocerebrosidase. Haematopoietic stem cell transplantation is the only available effective treatment. The engraftment from normal donors provides competent cells able to correct the metabolic defect. Umbilical cord blood cells have proved to significantly decrease complications and improve engraftment rate compared to adult marrow cells in haematopoietic stem cell transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For example, in children with Krabbe disease (demyelinating LSD) who received UCBCT before symptoms appeared, normal blood galactocerebrosidase levels, central nervous system myelination and continued developmental skill progress were observed. However, it is important to note that children undergoing transplantation after the appearance of the symptoms had minimal neurological improvements [21][22][23][24][25]. Similar results were obtained after UCBCT in patients with metachromatic leukodystrophy (also demyelinating LSD) [26,27].…”
Section: Introductionmentioning
confidence: 57%
“…For example, in children with Krabbe disease (demyelinating LSD) who received UCBCT before symptoms appeared, normal blood galactocerebrosidase levels, central nervous system myelination and continued developmental skill progress were observed. However, it is important to note that children undergoing transplantation after the appearance of the symptoms had minimal neurological improvements [21][22][23][24][25]. Similar results were obtained after UCBCT in patients with metachromatic leukodystrophy (also demyelinating LSD) [26,27].…”
Section: Introductionmentioning
confidence: 57%
“…However the polymorphism T546 has been reported to be present within the population at allele frequency of 40–45% . Clinical assays for GALC activity in peripheral blood have suggested that the T546 variant has half the activity of the I546 variant, contributing to the highly variable ‘normal’ activity levels within the general population . In order to test the effect of this polymorphism on GALC activity we generated stable expression constructs of each of these polymorphisms and selected high‐yield clones in order to purify milligram quantities of GALC for steady‐state kinetic studies (Figure A and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The galactosidase can hydrolyze HMU-βGal to produce specific fluorescence products under acidic conditions. The fluorescence value was measured by a F97 series fluorescence spectrophotometer at 365 and 460 nm (12)(13)(14). According to the standard curve and the specific fluorescence value, the activity of GALC enzyme can be calculated.…”
Section: Enzyme Activity Detectionmentioning
confidence: 99%